1992
DOI: 10.1152/jappl.1992.72.1.194
|View full text |Cite
|
Sign up to set email alerts
|

Noise-induced hypertension and magnesium in rats: relationship to microcirculation and calcium

Abstract: It has been demonstrated that audiogenic stress (AS) can induce elevation of arterial blood pressure (ABP) in animals and humans and that noise-induced hearing loss may be associated with alterations in Mg metabolism. Experiments were designed to determine whether 1) there is a causal relationship among environmental noise stress, serum and vascular tissue (aortas and portal veins) Mg contents, and development of hypertension and 2) such noise-induced hypertension has a microcirculatory basis and what the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 0 publications
2
61
0
1
Order By: Relevance
“…Magnesium deficiency, as assessed by decreased magnesium in the blood or tissues, and cardiovascular disease are linked [27,28]. In a recent review [29], none of the various circulating spasmogenic theories could satisfactorily account for coronary vasospasm in hyperthyroidism, and Miyagi et al [30] had shown magnesium to suppress coronary spastic angina.…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium deficiency, as assessed by decreased magnesium in the blood or tissues, and cardiovascular disease are linked [27,28]. In a recent review [29], none of the various circulating spasmogenic theories could satisfactorily account for coronary vasospasm in hyperthyroidism, and Miyagi et al [30] had shown magnesium to suppress coronary spastic angina.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant scavenging of ROS also potentially reduces vasoconstriction that occurs with ROS production [46, for review see 27]. One effect of magnesium is reduction of noise-induced vasoconstriction [67,[79][80][81].…”
mentioning
confidence: 99%
“…Moreover, dietary deficiency of Mg, under very-controlled laboratory conditions, in rats and rabbits has been shown to cause vascular remodeling concomitant with hypertension and atherogenesis (i.e., arteriolar wall hypertrophy and alterations in arterial wall matrices) of unknown origin [4,6,[15][16][17][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%